2015
DOI: 10.1016/j.bjp.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Chromenes from leaves of Calea pinnatifida and evaluation of their leishmanicidal activity

Abstract: BJP 88 1-4 Revista Brasileira de Farmacognosia xxx (2015) xxx-xxx w w w . s b f g n o s i a . o r g . b r / r e v i s t a a b s t r a c t Calea pinnatifida (R. Br.) Less., Asteraceae, is popularly known as "quebra-tudo", "cipó-cruz" or "aruca". This species is used in the folk medicine for the treatment of stomach pain, giardiasis and amoebiasis. The aim of this study was to isolate and identify chromenes from leaves of C. pinnatifida and evaluate their leishmanicidal activity. A fraction from leaves of C. pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Baker. Eupatoriochromene (165) and methyeupatoriochromene (166) are the predominant chromenes in Calea genus (Bohlmann, Bajupi, King, & Robinson, ; Bohlmann, Fritz, et al, ; Bohlmann, Gupta, Japukovic, King, & Robinson, ; Bohlmann, Gupta, Japukovic, King, & Robinson, ; Castro et al, ; Lima et al, ; Steinbeck et al, ).…”
Section: Chemical Constituentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Baker. Eupatoriochromene (165) and methyeupatoriochromene (166) are the predominant chromenes in Calea genus (Bohlmann, Bajupi, King, & Robinson, ; Bohlmann, Fritz, et al, ; Bohlmann, Gupta, Japukovic, King, & Robinson, ; Bohlmann, Gupta, Japukovic, King, & Robinson, ; Castro et al, ; Lima et al, ; Steinbeck et al, ).…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…C. pinnatifida is a subshrub plant found mainly in southern and southeastern Brazil. Lima et al () investigated leishmanicidal effect of four chromenes (165–168) isolated from hexane fraction of C. pinnatifida against L. amazonensis intracellular amastigotes. Chromenes 165 and 167 demonstrated a moderate leishmanicidal activity, inhibiting parasite intracellular growth in 39.3% and 32.3%, respectively.…”
Section: Biological Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…C. uniflora has been little studied. Previous studies showed that this plant is rich in constituents such as lactones, sesquiterpenes, flavonoids, saponins and derivatives of p-hydroxyacetophenone (Lima et al, 2015). Other phytochemical studies by Nascimento and Oliveira (2004) showed that C. uniflora contains the compounds, glucoside-5-deoxyflavone, 3',4',7-trihydroxyflavone-7-O-β-glucopyranoside, 2',4-dihydroxy-3-methoxychalcone-40-O-β-glucopyranoside and quercetin-3-O-β-galactopyranoside.…”
Section: Introductionmentioning
confidence: 99%
“…Some species of this genus were investigated for their medicinal properties including the following: Calea pinnatifida (Lima et al, 2015) with leishmanicidal activity; Calea urticifolia (Yamada et al, 2004) used to treat oliguria and gastroenteritis; Calea zacatechichi (Leonti et al, 2003) used for dermatological/respiratory ailments and gastrointestinal purposes; Calea serrata Less. (Ribeiro et al, 2008) used to treat ulcers and liver problems and Calea glomerata (Guerrero et al, 2002) used as an antihypertensive.…”
Section: Introductionmentioning
confidence: 99%